Pelatihan Media Online Dalam Upaya Meningkatkan Melek Informasi Kalangan Milineal pada Program Pembangunan di Desa Purbahayu - Nugraha, Aat Ruchiat; Novianti, Evi; Komala, Lukiati; Lukman, Syauqy; Sjoraida, Diah Fatma (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2019)
The presence of digital technology in the community has had a significant impact on the patterns of life behavior of urban and rural communities. Pangandaran is a new district in West Java, still has many developing villages. In developing villages, there is also exposure to increasingly massive digital communication used by the community. The involvement of the millennial generation as part of the village community in the digital era can provide open and innovative development opportunities to develop the potential of the village-owned. Based on this information, the implementation of community service in the village of Purbahayu was carried out by choosing the theme of online media training for millennial generations in order to improve information literacy in development using lecture, discussion, and simulation methods through the demonstration learning model approach. The results of the implementation of community service show that the millennial generation in Purbahayu village has increased knowledge that is evident from the many questions surrounding the use and use of online media for the development of village potential. Whereas behaviorally, the millennial generation in Purbahayu village has been exposed to various business services and financial services by the millennial generation habits in urban areas.